Factors that influence Malaysia generation Z consumers’ purchase intention during flash sales promotion - Saw, Yoke Teng; Tin, Ley Hui (2023)
With the booming of e-commerce and rising of many sellers and companies attributed to flash sales promotions, combined with the proliferation of Generation Z’s impact during flash sales promotions, and the increasing need of investigating their respective behaviors in the yet-to-studied Malaysian context, this research uses Theory of Reasoned Action (TRA) to determine the relationship between factors that are important with the Malaysia Generation Z consumers’ purchase intention during online flash sales promotion. The variables proposed in this research framework are utilitarian value and hedonic value which constitutes a consumer’s attitude, informational influence and normative influence which constitutes a consumer’s subjective norms and perceived perishability and perceived scarcity to account for the nature of effects created by flash sales strategies. After that, 6 respective hypotheses are developed. Quantitative method is then utilized by distributing questionnaires to collect a total of 280 respondents required particularly Generation Z in Malaysia aged from 16-25 to conduct this study’s analysis. The results conducted through the pilot test are all acceptable and SPSS Software Version 29 is used to analyze the data collected and come up with conclusions subsequently. Based on the findings obtained, both utilitarian value, hedonic value, informational influence and perceived perishability showed a significant effect on Malaysia Generation Z’s purchase intention during online flash sales promotion, whereas normative influence and perceived scarcity showed no significant influence on Malaysia Generation Z’s purchase intention during online flash sales promotion. As a result, our research provides implications to future researchers and marketers on a better insight and ways of designing a more effective and efficient online flash sales promotion. Limitations imposed are to prompt greater advanced research eventually explaining comprehensively the consumers’ behavior in this promising flash sales context.